The Effect of Discipline Development and Physical Work Environment on the Job Satisfaction of State Civil Apparatus (ASN) Functional Positions of the Cimahi City Education Office - Neni Andriani; RM Juddy Prabowo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Fostering good discipline and a good physical work environment will increase employee job satisfaction. Several phenomena at the Cimahi City Education Office show a decline in job satisfaction, including high employee absenteeism rates without explanation, disciplinary violations, and inadequate physical working conditions. This condition suggests that the development of discipline and physical work environment can affect employee job satisfaction. This study aims to find out how respondents respond to disciplinary coaching and physical work environment, and how employee job satisfaction. In addition, it aims to determine the influence of discipline developmentand physical work environment on the job satisfaction of ASN of the Functional Position of the Cimahi City Education Office both partially and simultaneously. This study uses a quantitative approach with a descriptive and associative research design. In this study, there were 82 respondents from ASN Functional Positions of the Cimahi City Education Office. The data collection technique was carried out by distributing questionnaires. The data analysis in this study used multiple linear regression analysis and determination coefficients. This study shows that the respondents' response to discipline developmentis included in the good criteria. Similarly, respondents' responses to the conditions of the physical work environment are included in the good criteria. Job satisfaction is included in the satisfaction criteria. In addition, this study shows that discipline developmenthas a positive effect on job satisfaction. This means that the better the Discipline development, the job satisfaction will increase. Similarly, the physical work environment has a positive effect on job satisfaction. This means that the better the physical work environment, the job satisfaction will increase. Discipline development and physical work environment affect the job satisfaction of ASN Functional Positions of the Cimahi City Education Office. This means that if the discipline and physical work environment are good, it can increase employee job satisfaction.